PUBLIC ACCOUNTING AS AN INSTRUMENT TO PROMOTE PUBLIC POLICIES TO REDUCE EDUCATIONAL INEQUALITIES (REMUNOM, 2025)
This article investigates public accounting as an essential tool for promoting educational policies aimed at reducing inequalities in Brazil. The research is based on the understanding that transparency, planning, and control in the management of public resources are crucial to ensuring that all students have equitable access to quality education. Using a qualitative approach, the study was based on a literature review and documentary analysis of legislation and information systems such as SIOPE, SIGPC, and SAGRES. The results reveal that, although most Brazilian states comply with legal requirements for budget allocation, there is a significant gap between fiscal compliance and the effectiveness of educational outcomes. The objective of the research is to analyze how these accounting instruments contribute to the effectiveness of public education policies, promoting social, economic, and sustainable development in all Brazilian regions. The study points to persistent challenges, such as heterogeneity in resource allocation and a considerable drop in public investment in education per student between 2015 and 2021, which remained well below the OECD average. It concludes that public accounting must evolve beyond simple accountability and be used as a more comprehensive tool for planning, monitoring, and evaluating spending